The Relationship Between Exposure to Cigarette Smoke and the Incidence of Acute Respiratory Infections (ARI) in Children Under Five: Cigarette Smoke Exposure and ARI in Children Under Five - Eppang, Yudiarsi; Muldaniyah (Innovative Approaches in Health Science Journal, 2025)
Background: Acute respiratory infections (ARI) remain a major health problem in children under five. One of the risk factors associated with ARI is exposure to cigarette smoke. This study aimed to examine the relationship between exposure to cigarette smoke and the incidence of ARI among children under five at Kapasa Health Center, Makassar City, in 2024. Methods: This study employed a quantitative design with a cross-sectional approach. A total of 44 parents or family members of children under five were recruited using a non-probability sampling technique. Data were analyzed using the Chi-Square statistical test to determine the association between exposure to cigarette smoke and the incidence of ARI. Results: The Chi-Square test showed a p-value of 0.022, which was lower than the significance level of 0.05. This finding indicates a statistically significant relationship between exposure to cigarette smoke and the incidence of ARI in children under five. Conclusion: Exposure to cigarette smoke is significantly associated with the occurrence of ARI in children under five at Kapasa Health Center, Makassar City. Preventive measures to reduce children’s exposure to cigarette smoke are urgently needed to lower the risk of ARI.